The Apertochrysa prasina group (Neuroptera: Chrysopidae), with a key to the European species - Duelli, Peter; Henry, Charles S. (Zootaxa, 2022)
All nine presently known European species of the Apertochrysa prasina group (formerly the Pseudomallada prasinus group) are diagnosed. Separate keys for the identification of living and preserved specimens of each sex are presented. For males, the “furwing” trait (increased numbers of setae on costal crossveins) is often crucial for identification, especially in preserved specimens. In some cases, females of the newly recognized prasinoid species (Ap1, Ap2, Ap3) are impossible to distinguish without live coloration. This is largely why the three “new” species are difficult to assign to one of the many old (often female) type specimens of former prasinoid species or varieties, which had been synonymized with Chrysopa prasina in the past.